MIDDLE ENGLISH: ENGLISH OR FRENGLISH? - L.M. Ikalyuk; U.T. Tatsakovych (Vasyl Stefanyk Precarpathian National University, 2015)
The article focuses on a general description of Middle English considering the impact of the French language on its development during this period. Despite an extensive number of French borrowings in different layers of the English language, the language remained English and its predominant features were still those of Germanic origin.